Urine Tuberculosis Lipoarabinomannan Predicts Mortality in Hospitalized Human Immunodeficiency Virus-Infected Children - LaCourse, Sylvia M (Clin Infect Dis, 2018)
Despite diagnostic performance limitations, urine lipoarabinomannan (LAM) predicts death in human immunodeficiency virus (HIV)–infected adults with tuberculosis. Pediatric data are limited. Among 137 hospitalized HIV-infected children, mortality was 4.9-fold higher among those with positive LAM (127 vs 31 per 100 person-years; adjusted hazard ratio, 4.92; 95% confidence interval [CI], 1.79–13.49; P = .002). Lipoarabinomannan identifies HIV-infected children at risk for death potentially missed by respiratory sampling. CLINICAL TRIALS REGISTRATION: NCT02063880.